Effect of Fluctuating High Temperatures on House Flies (Diptera: Muscidae) and Their Principal Parasitoids (Muscidifurax spp. and Spalangia spp. [Hymenoptera: Pteromalidae]) From the United States. Issue 6 (14th June 2019) - Geden, Christopher J; Biale, Haim; Chiel, Elad; Johnson, Dana M
Abstract: Colonies of house flies ( Musca domestica L. [Diptera: Muscidae]) and four species of parasitoids ( Muscidifurax raptor Girault and Sanders, Muscidifurax zaraptor Kogan and Legner, Spalangia cameroni Perkins and Spalangia endius Walker) were established by making collections from dairy farms near Bell, FL, Beatrice, NE, Minneapolis, MN, and San Jacinto, CA. Colonies were assessed for heat tolerance by comparing life history parameters at 25–27°C and fluctuating hot (26.7–41.7°C) temperatures. Muscidifurax raptor, S. cameroni, and S. endius produced 24–28% as many progeny under hot conditions as at 25°C. Colonies of M. zaraptor were more heat-tolerant and produced an average 46.9% as many progeny under the hot regime compared with moderate conditions. There was little evidence for higher heat tolerance in parasitoid populations from historically hot locations (CA desert and FL). Colonies of M. raptor and S. endius that had been in culture for 24 yr were the least heat-tolerant with regard to progeny production. House flies collected from the same locations varied little in longevity, fecundity, or egg-to-adult survival under either hot or moderate regimes. Flies reared under hot conditions laid about half as many eggs (89/female) and had about half the egg–adult survival rate (47.3%) under hot compared with moderate conditions, indicating that heat stress had less effect on flies than on all of the parasitoids except M. zaraptor . An attempt to select for heat tolerance in flies by subjecting them to incremental increases in rearing temperatures for 20 generations resulted in little change in tolerance among the selected flies.